Ultrasound and MRI Findings of Giant Cell Fibroblastoma in the Abdominal Wall: Radiologic-Pathologic Correlations - Min, Soyoon; Park, Sun-Young; Seo, Jinwon; Koh, Sung Hye; Lee, Kwanseop (Journal of the Korean Society of Radiology, 2020)
Giant cell fibroblastoma (GCF) is a rare soft-tissue sarcoma of fibroblastic origin. To the best of our knowledge, only one brief description of the MRI findings of GCF exists in the pathologic literature. Herein, we report a case of histologically proven GCF in a 3-year-old boy who underwent ultrasonography and MRI of a superficial mass in the abdominal wall.